Nicotinic acetylcholine receptor-mediated GABAergic inputs to cholinergic interneurons in the striosomes and the matrix compartments of the mouse striatum. (June 2016) - Inoue, Ritsuko; Suzuki, Takeo; Nishimura, Kinya; Miura, Masami
Abstract: The striatum consists of two neurochemically distinct compartments: the striosomes (or patches) and the extrastriosomal matrix. Although striatal neurons are strongly innervated by intrinsic cholinergic interneurons, acetylcholinesterase is expressed more abundantly in the matrix than in the striosomes. At present, little is known about the different cholinergic functions of the striatal compartments. In this study, we examined gamma-aminobutyric acidergic (GABAergic) inputs to cholinergic interneurons in both compartments. We found that nicotinic receptor-mediated GABAergic responses were evoked more frequently in the matrix than in the striosomes. Furthermore, a single action potential of cholinergic neurons induced nicotinic receptor-mediated GABAergic inputs to the cholinergic neurons themselves, suggesting mutual connections that shape the temporal firing pattern of cholinergic neurons. The nicotinic receptor-mediated GABAergic responses were attenuated by continuous application of acetylcholine or the acetylcholinesterase inhibitor eserine and were enhanced by desformylflustrabromine, a positive allosteric modulator of the α4β2 subunit containing a nicotinic receptor. These results suggest that the nicotinic impact on the GABAergic responses are not uniform despite the massive and continuous cholinergic innervation. It has been reported that differential activation of neurons in the striosomes and the matrix produce a repetitive behavior called stereotypy. Drugs acting on α4β2 nicotinic receptors might provide potential tools for moderating the imbalanced activities between the compartments. Highlights: Nicotinic receptor-mediated IPSCs are prominent in matrix cholinergic neurons. The nicotinic responses are attenuated by acetylcholine or eserine. Desformylflustrabromine has facilitating effects on the nicotinic response.